Poverty and the Political Economy of Baby Merchandizing in Nigeria - Oke, Leke; J. M., Oluwaleye (Advances in Social Sciences Research Journal, 2017)
The correlation between poverty and societal ills is underscored in the myriads of evils plaguing human societies including Nigeria. One of such ills, baby trading, that had hitherto been tagged a taboo in Nigeria especially among the Yorubas, in the South-West, is beginning to fade away. The high level of poverty among Nigerians culminating in the feminization of poverty has dealt a dastard blow to human dignity especially that of women. This is to the effect that mothers that were hitherto the ‘treasured gold’ have become the agents in the hands of social marauders conniving with their male folk to perpetuate the act of commoditizing babies contrary to the prevailing belief that babies were heavenly treasures that are given mainly by God and can never be commoditized. Thus, in recent times one is inundated with stories of women trading in babies for pecuniary gain occasioned merely by poverty, wants and societal decay. Such decadence is heightened by the level of underdevelopment in the country which have thrown up a lot of challenges for the citizens and opened a bizarre of activities that are deleterious not only to the development of the state but have been damaging to its sustainability as a corporate entity. Utilizing secondary and primary data, the paper discusses the insidious problem of baby trading and its implications on crave for development in Nigeria. It concludes that barring divine intervention the menace will continue unabated unless government intervenes by cushion the effects of corruption on Nigerians, judiciously and fairly redistribute the commonwealth and economically empowered the citizens, especially the womenfolk, towards national development.